A hidden Megasoma Kirby species under the enigmatic genus Gibboryctes Endrödi (Coleoptera: Scarabaeidae: Dynastinae) - Costa, Leidiane O.; Duarte, Paulo R. M.; Iannuzzi, Luciana; Grossi, Paschoal C. (Zootaxa, 2021)
Gibboryctes Endrödi, 1974 (Coleoptera: Scarabaeidae: Dynastinae: Oryctini) is an uncommon Neotropical genus comprising five valid species (Gasca-Álvarez & Ratcliffe 2011; Dupuis 2019). Endrödi (1974) established the genus based on Gibboryctes szelenyii Endrödi, 1974 and defined it by the absence of sexual dimorphism; short, triangular, and pointed clypeus; bidentate mandibles projected beyond the anterior clypeal margin; and protibiae quadridentate. After that, Gibboryctes waldenfelsi (Endrödi, 1977) and Gibboryctes gracilicornis (Prell, 1912) were assigned to Gibboryctes, from Strategus Kirby, 1828 and Heterogomphus Burmeister, 1847, respectively (Ratcliffe & Dechambre 1983; Dupuis & Dechambre 2008). Gibboryctes bollei Dechambre, 2006 and Gibboryctes impunctatus Dupuis, 2019 were subsequently described.